1972
DOI: 10.1021/ja00756a036
|View full text |Cite
|
Sign up to set email alerts
|

Novel route to racemization of sulfoxides

Abstract: and Sims4 have shown that 3 refluxed in 60% aqueous acetone for 36 hr produced a large amount of trans-9,10-dihydroxy-9,10-dihydrophenanthrene. This is consistent with Sn2 attack by water on the epoxides.Unfortunately, because of its symmetry the question of the importance of the NIH shift on 3 cannot be detected. Thus, 3 most certainly hydrolyzes in an analogous manner to simple epoxides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1972
1972
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…4b for CD spectroscopy of (S)- 18A and (R)- 18B ). Sulfoxide could racemize under 6 M HClO 4 40. Under the biorelevant acidic or basic conditions tested, there was no detectable sulfoxide racemization.…”
Section: Resultsmentioning
confidence: 87%
“…4b for CD spectroscopy of (S)- 18A and (R)- 18B ). Sulfoxide could racemize under 6 M HClO 4 40. Under the biorelevant acidic or basic conditions tested, there was no detectable sulfoxide racemization.…”
Section: Resultsmentioning
confidence: 87%
“…It had previously been demonstrated that selected enantiopure sulfoxides can undergo acid-catalyzed racemization of stereochemistry at sulfur 47 and it was believed that the proximal hydroxyl of 3a could play a role in directing a possible inversion of the sulfinyl configuration. The addition of a small amount of trifluoroacetic acid (TFA) brought about immediate changes in the 1 H NMR spectrum of the sample.…”
Section: Resultsmentioning
confidence: 99%
“…of sulfoxide this value decreased from 22 to 7 μS cm −1 after 24 h. At the same time, as reported in Table 1, longer reaction times did not guarantee any increase of the yield, when lower amounts of 4 were used, but a decrease of the enantiomeric purity of the sulfoxide was observed without affecting the enantioselectivity of the allylation. Even if (R)-methyl p-tolyl sulfoxide is reported to be configurationally stable and it gives inversion only at high temperature 21 or in the presence of acids, 22 the possibility to form tetracoordinate sulfurane species can lead to the loss of enantiomeric purity and deactivation of sulfoxide. 14b,15 Other studies are underway to investigate this fascinating behaviour that combines the chemistry of silicon and sulfur compounds in a unique fashion with important implications in a fundamental organic transformation like enantioselective allylation of aldehydes.…”
Section: Reaction Mechanismmentioning
confidence: 99%